"Features of Far North Life Pictured by the Bartlett-Academy of Natural Sciences Greenland Expedition" (Philadelphia Evening Bulletin, 1930)
"This is the manner in which the young Eskimo girl takes her baby sister for a ride up in the Greenland hinterland, where the country is a bit rough for baby coaches. This style of hitching baby on the back of a sister or mother is also an American Indian custom." With clipping